2017
DOI: 10.3168/jds.2017-13321
|View full text |Cite
|
Sign up to set email alerts
|

Grain challenge affects systemic and hepatic molecular biomarkers of inflammation, stress, and metabolic responses to a greater extent in Holstein than Jersey cows

Abstract: Long-term feeding of high-grain diets to dairy cows often results in systemic inflammation characterized by alterations in acute-phase proteins and other biomarkers, both in plasma and immune-responsive tissues like the liver. The molecular and systemic changes that characterize an acute grain feeding challenge remain unclear. The current study involved 6 Holstein and 6 Jersey cows in a replicated 2 × 2 Latin square. Periods (10 d) were divided into 4 stages (S): S1, d 1 to 3, served as baseline with total mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 61 publications
6
17
2
2
Order By: Relevance
“…Activation of MTOR has been associated with increased lipogenesis Liu et al, 2016). Xu et al (2017) indicated that an upregulation in MTOR in Jersey cows fed high-grain diets as a challenge could be responsible for increased hepatic lipogenesis. In the current study, downregulation of MTOR for cows in POS could explain the decrease in serum cholesterol for this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of MTOR has been associated with increased lipogenesis Liu et al, 2016). Xu et al (2017) indicated that an upregulation in MTOR in Jersey cows fed high-grain diets as a challenge could be responsible for increased hepatic lipogenesis. In the current study, downregulation of MTOR for cows in POS could explain the decrease in serum cholesterol for this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed in Pate and Cardoso (2018), where hepatic NFKB1 expression was greater in cows challenged with AF compared with cows without AF challenge. Additionally, Xu et al (2017) reported increased hepatic NFKB1 expression when a grain challenge was fed to Holstein cows. Increased NFKB1 expression has been shown to regulate other inflammatory genes, such as TNFA and IL6, which are proinflammatory cytokines (Baker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the well-established effects of ruminal acidosis on epithelial integrity and molecular responses, there has been interest in using genome-enabled technologies for evaluating the post-ruminal effect of acidosis. Examples include work with mRNA and/or protein expression in the liver (Chang et al, 2015;Xu et al, 2017), white blood cells (Stefanska et al, 2017) and mammary gland (Jin et al, 2016;. In regards to the liver, acute (1 day) or chronic (10 weeks) ruminal acidosis in Holstein cows induced by feeding a high-grain diet causes upregulation of inflammatory mediators (Chang et al, 2015;Xu et al, 2017).…”
Section: Genomic Alterations and Implications On Health: Rumen Epithementioning
confidence: 99%
“…Examples include work with mRNA and/or protein expression in the liver (Chang et al, 2015;Xu et al, 2017), white blood cells (Stefanska et al, 2017) and mammary gland (Jin et al, 2016;. In regards to the liver, acute (1 day) or chronic (10 weeks) ruminal acidosis in Holstein cows induced by feeding a high-grain diet causes upregulation of inflammatory mediators (Chang et al, 2015;Xu et al, 2017). Hence, the pro-inflammatory response to acidosis is not unique to rumen epithelium and even extends to circulating white blood cells (Stefanska et al, 2017) and the mammary gland .…”
Section: Genomic Alterations and Implications On Health: Rumen Epithementioning
confidence: 99%
See 1 more Smart Citation